Stambuł w świetle księżyca – Boğaziçi Mehtapları Abdülhaka Şinasiego Hisara1 - Filipowska, Sylwia (Studia Azjatystyczne, 2015)
Istanbul is one of the most popular motives in the writings of Abdülhak Şinasi Hisar (1887-1963). The famous Turkish novelist used to complain that even the inhabitants of Istanbul have forgotten the history and traditions of their city. One of his memories, called Boğaziçi Mehtapları, refers to the custom called mehtap, which was still cultivated at the end of 19th century, but has been completely forgotten forty years later. Mehtap was a kind of a trip made in special boats called kayık on waters of the Bosphorus, performed in the moonlight with accompaniment of music. A.Ş. Hisar presents all details regarding to the organizational part of mehtaps, which is really important from the historical and ethnographical point of view, but the article focuses on literary value of these memories, which created a poetic picture of Istanbul in the moonlight.